025 The neural correlates of doorway freezing in parkinson's disease. Issue 6 (24th May 2018) - Matar, Elie; Shine, James M; Gilat, Moran; Ehgoetz-Martens, Kaylena; Ward, Phillip B; Frank, Michael J; Moustafa, Ahmed; Naismith, Sharon L; Lewis, Simon JG
Abstract : Introduction: Freezing of gait (FOG) in Parkinson's disease (PD) is a disabling symptom of advanced PD and is frequently triggered upon passing through narrow spaces such as doorways. 1 Despite being common, the mechanisms underlying this phenomenon are poorly understood. We have previously shown that increased footstep latency in a virtual reality (VR) environment is a surrogate measure of FOG. 2 In this study we aimed to model doorway freezing utilising the VR paradigm in conjunction with functional magnetic resonance imaging (fMRI) to determine the neural correlates of this phenomenon. Methods: In our study, nineteen patients who routinely experience FOG performed a previously validated VR gait paradigm 3 where they used foot-pedals to navigate a series of doorways. Patients underwent testing randomised between both their 'ON' and 'OFF' medication states. Task performance in conjunction with blood oxygenation level dependent signal changes were compared within each patient. Results: We were able to reproduce the finding that patients in the OFF state demonstrated significantly longer 'footstep' latencies as they passed through a doorway in the VR environment compared to the ON state. As seen clinically with FOG this locomotive delay was primarily triggered by narrow doorways rather than wide doorways. fMRI analysis revealed that doorway-provoked footstep delay was associated with selective hypoactivation in the pre-supplementary motor area (pSMA) bilaterally. Task-based functional connectivity analyses showed that this delay was inversely correlated with the degree of functional connectivity between the pSMA and the subthalamic nucleus (STN) across both hemispheres. Furthermore, increased frequency of prolonged footstep latency was associated with increased connectivity between the bilateral STN. Conclusion: These findings suggest that the effect of environmental cues on triggering FOG reflects a degree of impaired processing within the pSMA and disrupted signalling between the pSMA and STN, thus implicating the 'hyperdirect' pathway in the generation of this phenomenon. References: . Giladi N, Treves TA, Simon ES, Shabtai H, Orlov Y, Kandinov B, Paleacu D, Korczyn AD. Freezing of gait in patients with advanced Parkinson's disease. J Neural Transm (Vienna)2001;108:53–61. . Matar E, Shine JM, Naismith SL, Lewis SJ.Virtual realitywalking and dopamine: opening new doorways to understanding freezing of gait in Parkinson's disease. J Neurol Sci 2014;344:182–5. . Shine JM, Matar E, Bolitho SJ, Dilda V, Morris TR, Naismith SL, Moore ST, Lewis SJ. Modelling freezing of gait in Parkinson's disease with a virtual reality paradigm. Gait Posture2013;38:104–8.